Association between the intensity of obstructive sleep apnea and skeletal alterations in the face and hyoid bone - Soares,Manoela M. (2022)
Abstract Introduction The association between the intensity of obstructive sleep apnea and skeletal alterations in the face and hyoid bone is still scarcely addressed in the literature. Objective To evaluate whether the intensity of obstructive sleep apnea is associated with craniofacial alterations and the position of the hyoid bone in children with mixed dentition. Methods 76 children aged 7 to 10 years old were examined by otorhinolaryngological evaluation, polysomnography, and orthodontic assessment, including cephalometry. The participants were divided in 3 groups: primary snoring, mild obstructive sleep apnea and moderate to severe obstructive sleep apnea. Cephalometric measures of the face and hyoid bone were assessed. These measures were compared among the different groups by unpaired Student's t test. Moreover, these measures were correlated with the patient's obstructive apnea and hypopnea index variable using Pearson's correlation test. Results Of the 76 children, 14 belonged to group 1, with primary snoring; 46 to group 2, with mild obstructive sleep apnea; and 16 to group 3, with moderate-severe obstructive sleep apnea. There was no difference between the groups regarding the craniofacial variables. Children with obstructive sleep apnea showed a longer distance from the hyoid bone to the mandibular plane when compared to the primary snoring group (p < 0.05). Between the two obstructive sleep apnea subgroups, patients with moderate or severe disease showed significantly shorter horizontal distance between the hyoid bone and the posterior pharyngeal wall (p < 0.05), when compared to the groups with mild obstructive sleep apnea. We also observed a significant positive correlation between obstructive apnea and hypopnea index and the distance from the hyoid to the mandibular plane (p < 0.05) as well as a significant negative association between obstructive apnea and hypopnea index and the horizontal distance from the hyoid to the posterior pharyngeal wall (p < 0.01). Conclusion We did not observe any association between obstructive sleep apnea and linear lateral alterations of the face. In contrast, there is a direct association between obstructive sleep apnea severity and the inferior and posterior position of the hyoid bone in children aged 7 to 10 years old.